Association between duration of residence with gingival pigmentation in Nuha District, East Luwu Regency, South Sulawesi, Indonesia - Rasmidar Samad; Qushay U. Malinta (Journal of Dentomaxillofacial Science, 2017)
Objective : Gingival pigmentation (changes of the gingival color) from brown to black discoloration may occur due to exogenous and endogenous factor. Increased concentration of heavy metal in the blood has been known to be one of the exogenous factors that could lead to gingival pigmentation. Nuha is a sub-district in South Sulawesi which soil contains high concentration of nickel and other heavy metals. Heavy metal contaminations in the water, soil, or air have detrimental effects on human health, particularly the oral cavity.Material and Methods : This study proposed to determine the association between duration of residence with gingival pigmentation to the community of Nuha District of East Luwu society. This study was a descriptive observational with cross-sectional study design.Results : The population in this study was all of the Nuha residents. The sampling technique used was simple two-stage cluster sampling. Gingival pigmentation in this study was measured using Dummet Oral Pigmentation Index (DOPI).Conclusion : The data obtained showed significant association between duration of residence with maxillar and mandibular gingival pigmentation in the residents of Nuha District of Luwu Timur. p-value for maxillar DOPI was 0.003 and for mandibular DOPI was 0.000.Â Â